(untitled) (Baghdad Science Journal, 2023)
Microalgae have been increasingly used for wastewater treatment due to their capacity to assimilate nutrients. Samples of wastewater were taken from the Erbil wastewater channel near Dhahibha village in northern Iraq. The microalga Coelastrella sp. was used in three doses (0.2, 1, and 2g. l-1) in this experiment for 21 days, samples were periodically (every 3 days) analyzed for physicochemical parameters such as pH, EC, Phosphate, Nitrate, and BOD5, in addition to, Chlorophyll a concentration. Results showed that the highest dose 2g.l-1 was the most effective dose for removing nutrients, confirmed by significant differences (p≤0.05) between all doses. The highest removal percentage was recorded for ammonium pass 96% followed by NO3 with 95%, while BOD5 ranged from 88.7 to 93.5%. Decreases in nutrients coincided with an increase in chlorophyll-a content with the highest biomass on the 17th day of the experiment reaching 1.43 mg. l-1.